Kenya : Request for a Three-Year Arrangement Under the Extended Credit Facility-Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Kenya. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
Kenya's economy is bouncing back following multiple shocks between 2008 and 2009. The program targets a gradual reduction in the central government primary balance through tax reform and strict control of current spending to bring the debt-to-GDP ratio below 45 percent at the end of the program period. Tax policy reform will focus on the VAT, streamlining tax incentives, and eliminating loopholes. Kenya has made significant strides in domestic revenue mobilization, but redesigning the tax structure is a key priority.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Kenya